New insights on the middle Givetian/middle Frasnian palynofloras from the Phyllite-Quartzite Formation in the Neves-Corvo mine region (Iberian Pyrite Belt, Portugal) - Mendes, Márcia (2020)
ABSTRACT: A detailed palynostratigraphic study of two Somincor/Lundin Mining exploration drill holes intercepting the Phyllite-Quartzite (PQ) Formation in the geological basement of the Neves-Corvo mine region (Portuguese sector of the Iberian Pyrite Belt – IPB) allowed to first recognise the oldest ages for this formation in this region, ranging from midGivetian/midFrasnian (base unknown) to late Famennian. The TA Miospore Biozone (Cristatisporites triangulatus-Ancyrospora ancyrea) of middle Givetian age (Middle Devonian) was identified in NK30B-1 drill hole (Lombador North mine sector), whereas the BM Miospore Biozone (Verrucosisporites bulliferus-Lophozonotriletes media) and IV Miospore Biozone (based in the first occurrence of Rugospora bricei and Diducites cf. poljessicus) of middle Frasnian (Late Devonian) age were both recognised in drill hole SJ32 (Corvo-Semblana mine sector). The common presence of Early-Middle Devonian reworked spores, as well as similar inherited zircon ages may suggest that the lower PQ Formation age is not yet known. At Neves-Corvo mine, the Volcano-Sedimentary Complex is deposited directly above the PQ basement, spanning different ages, pointing out two major unconformities, a VSC/upper and/or lower PQ sequences and an upper PQ/lower PQ sequences. A palynostratigraphic correlation of the lowermost Phyllite-Quartzite Formation across the IPB is established. Phyllite-Quartzite Formation palynoassemblage of Neves-Corvo region is compared with lowermost PQ assemblages recovered in the NW sector of IPB (S. Francisco da Serra and Lousal-Caveira mine structures, Portugal) and in E sectors of the IPB in Spain (Gerena-El Garrobo section). The similar palynological record (also including the same reworked taxa signature) and ages obtained, suggests identical sedimentary provenance, close paleogeographic domain and temporal affinity throughout the lowermost IPB Phyllite-Quartzite Formation.